Endoscopic ultrasound-guided biliary drainage for malignant biliary obstruction with surgically altered anatomy: a multicenter prospective registration study. (July 2020) - Minaga, Kosuke; Takenaka, Mamoru; Ogura, Takeshi; Tamura, Takashi; Kuroda, Taira; Kaku, Toyoma; Uenoyama, Yoshito; Noguchi, Chishio; Nishikiori, Hidefumi; Imai, Hajime; Sagami, Ryota; Fujimori, Nao; et al.
Background: Endoscopic treatment for malignant biliary obstruction (MBO) in patients bearing surgically altered anatomy (SAA) is not well-established. Although endoscopic ultrasound-guided biliary drainage (EUS-BD) has emerged as a new treatment option for MBO, limited data are available regarding the efficacy and safety of EUS-BD in patients with SAA. We conducted a multicenter prospective registration study to evaluate the efficacy and safety of EUS-BD in this population. Methods: This study involved 10 referral centers in Japan. Patients with SAA who were scheduled to receive EUS-BD for unresectable MBO between May 2016 and September 2018 were prospectively registered. The primary endpoint was technical success and the secondary outcomes were clinical success, procedure time, procedure-related adverse events (AEs), stent patency, and overall survival. Results: In total, 40 patients were prospectively enrolled. The surgical reconstruction methods were gastrectomy with Roux-en-Y reconstruction (47.5%), gastrectomy with Billroth-II reconstruction (15%), pancreaticoduodenectomy (27.5%), and hepaticojejunostomy with Roux-en-Y reconstruction (10%). EUS-BD was performed for primary biliary drainage in 31 patients and for rescue biliary drainage in nine patients. Transmural stenting alone (60%), antegrade stenting alone (5%), and a combination of the two techniques (35%) were selected for patients treated with EUS-BD. Technical and clinical success rates were 100% (95% confidence interval, 91.2–100.0%) and 95% (95% confidence interval, 83.1–99.4%), respectively. Mean procedure time was 36.5 min. Early AEs were noted in six patients (15%): three self-limited bile leak, one bile peritonitis, and two pneumoperitonea. Late AEs occurred in six patients (15%): one jejunal ulcer and five stent occlusions. Stent patency rate after 3 months of survival was 95.7% (22/23). Median overall survival was 96 days. Conclusion: EUS-BD for MBO in patients with SAA appears to be effective and safe not only as a rescue drainage technique after failed endoscopic retrograde cholangiography but also as a primary drainage technique. Clinical Trial Registration: UMIN000022101